(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Medical abortion is a revolution of the 21st century. During the COVID-19 pandemic, there were a number of issues in the medical fields, including abortion. Since in the Republic of Uzbekistan there were a number of inconveniences with a visit and further observation by a doctor. To achieve the best result, we conducted a clinical study and optimization of medical abortion using a number of useful and methods that helped women in our country during the pandemic to conduct a confidential, safe abortion on an outpatient basis without visiting a doctor.